Application Of The Ipswich Touch Test (IPTT) Method To Detect Diabetic Neuropathy (Penerapan Metode Ipswich Touch Test Untuk Mendeteksi Neuropati Diabetik) - Gita Cahyani; Ta'adi Samsuri; Anna Jumatul (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2022)
ABSTRACTNeuropathy is the classic and most common complication of DM. One of the early detection of diabetic sensory neuropathy is the Ipswich Touch Test. This study aims to analyze, compile and examine the results of published research articles containing the application of the IpTT method in detecting diabetic neuropathy. Desain of this research is a literature review. Article searches were carried out comprehensively through national and international indexed research journals databases such as Pubmed, Elsevier Clinical Key, and Google Scholar. who met the inclusion and exclusion criteria. The research articles obtained were 6 articles, then all the articles obtained were synthesized and combined. The results of the analysis of six journals, there are five research journals with cross-sectional study and systematic review methods, stated that the IpTT examination is significant for detecting diabetic neuropathy, which is evidenced by having a sensitivity ranging from 51-83.3% and a specificity of 90-96, 6% which means it has higher accuracy than the monofilament test. Meanwhile, another journal that uses a cross-sectional study states that the results are not significant/there is no difference between the IpTT examination and the monofilament test, this is because the researchers did not characterize DM respondents in their research. In general, five of the six journals recommend that the IpTT examination can be a reliable method, does not require special costs or tools, and is easy to apply in primary health care and in inpatient care for early detection of diabetic neuropathy.